1974
DOI: 10.1161/01.cir.49.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Heart Rate and Age on the Systolic and Diastolic Time Intervals in Children

Abstract: The systolic time intervals have been measured in 76 normal children, aged 1 month to 15 years, from simultaneous recordings of the electrocardiogram, phonocardiogram and carotid arterial pulse or apexcardiogram (left or right). Four different statistical methods were applied to study the separate influence of heart rate (HR) and age on these intervals. Left ventricular ejection time (LVET) had a highly significant correlation with HR but none with age. Age alone had a slight but significant influence on pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
2

Year Published

1978
1978
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 20 publications
5
19
0
2
Order By: Relevance
“…In this study we found the PEP/LVET ratio to be essentially independent of both age and heart rate, as was found in the study of Spitaels et al 5 and as has been found in adults.' Although by the statistical methods used, regression equations were derived relating the PEP/LVET ratio to heart rate in males and to age in females, the correlation in both cases is very low and probably does not justify the use of these equations in practice.…”
Section: The Pep/lvet Ratiosupporting
confidence: 90%
See 1 more Smart Citation
“…In this study we found the PEP/LVET ratio to be essentially independent of both age and heart rate, as was found in the study of Spitaels et al 5 and as has been found in adults.' Although by the statistical methods used, regression equations were derived relating the PEP/LVET ratio to heart rate in males and to age in females, the correlation in both cases is very low and probably does not justify the use of these equations in practice.…”
Section: The Pep/lvet Ratiosupporting
confidence: 90%
“…This was made possible by the work of Weissler and his associates, who established regression equations for the normal intervals in relation to heart rate in adults.' There are only a few studies, however, on systolic time intervals in children, and these studies differ in the techniques used and have had conflicting results in the normal standards relative to heart rate and age.2 5 In the present study we have used the precise techniques established for adults by Weissler and his associates' 6 to derive regression equations for systolic time intervals in normal children to be used as reliable standards for the assessment of left ventricular performance in this age group.…”
mentioning
confidence: 99%
“…18 Various authors have shown that heart rate is the dominant factor influencing cardiac time intervals. 19 The differential effect of heart rate on systolic versus diastolic duration may be a mechanism for cardiac dysfunction and a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…PEP and LVET are easily corrected for changes in pulse rate [22,23,28,38]. The quotient PEP/LVET is less HR-dependent [6,14,38] and has been considered to be the single most useful index of left ventricular performance from the systolic time intervals [14].…”
Section: Discussionmentioning
confidence: 99%